(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The tremendous growth in population, globalization and industrialization have led to the development of the construction sectors. The construction sector contributes a majorly to the development of the country based on its infrastructural needs. Also, concrete turns out to be the best and greatest construction building material in the global scenario. Concrete has become a highly sort out construction material because it could be cast in-situ and precast satisfying the construction feasibilities. The concrete is bifurcated into special types of concrete for decades. One such special type includes Self-Compacting Concrete (SCC). SCC has gained high priority among other types of special concrete. SCC has got a unique superior property of easy flowing nature. The greatest credit of using SCC is that it is user-friendly because it does not require compaction, consumes less time, and provides a smooth surface and textured finish. It does not require skilled labour. These advantages have scored and drawn the attention of the construction sector. Nowadays, most of the ready-mix plants use SCC to serve their building. The findings from the current investigation are summarized below. The workability of concrete increase with the increase in the variation in the partially replacement of cement with nano silica and Coarse aggregate with the pumice light weight aggregate. The maximum compressive strength of M40 grade for 7 days of all the mixed combinations is found to be 38.88 N/mm2 when coarse aggregate was replaced with 36% by pumice light weight aggregate and binder i.e., cement with 0.8% by nano silica.The maximum compressive strength M40 grade of concrete for 28 days of all the mixed combinations is found to be 54.42 N/mm2 when coarse aggregate was replaced with 36% by pumice light weight aggregate and binder i.e., cement with 1.6% by nano silica. The maximum split tensile strength M40 grade for 7 days of all the mixed combinations is found to be 3.46 N/mm2 when coarse aggregate was replaced with 36% by pumice light weight aggregate and binder i.e., cement with 0.8% by nano silica. The maximum split tensile strength M40 grade for 28 days of all the mixed combinations is found to be 5.85N/mm2 when coarse aggregate was replaced with 36% by pumice light weight aggregate and binder i.e., cement with 1.2 % by nano silica respectively. The maximum flexural strength M40 grade for 7 days and 28 days of all the mixed combinations is found to be 6.78 N/mm2& 9.24 N/mm2 respectively. when coarse aggregate was replaced with 36% by pumice light weight aggregate and cement with 1.6 % by nano silica respectively. By using of waste materials such as pumice light weight aggregate and nano silica in concrete the structure becomes light weight and economical and environment can be also protected for pollution etc.